Effects of moderate-intensity exercise on social health and physical and mental health of methamphetamine-dependent individuals: A randomized controlled trial - Xu, Jisheng; Zhu, Zhicheng; Liang, Xin; Huang, Qiuyue; Zheng, TianZhen; Li, Xue (Frontiers in Psychiatry, 2022)
Objective: Methamphetamine (MA)-dependent individuals’ health problems are widespread and need to be solved urgently. Exercise is considered a potential treatment for MA dependents. The study aimed to determine the effects of a 12-week aerobic exercise on the social, physical, and mental health of MA-dependent individuals. Methods: Sixty MA-dependent individuals were randomly assigned into two groups. Subjects in the exercise group (n=30) received an exercise intervention five days a week for 60 minutes each for 12 weeks. Subjects in the control group (n=30) received regular corrective rehabilitation without exercise in the same setting. Outcome measures, including questionnaires (quality of life scale for drug addiction (QOL-DA), self-rating anxiety scale (SAS), self-rating depression scale (SDS), and Pittsburgh sleep quality index (PSQI)) and physical fitness, were arranged the day before the start of the intervention and the day after the end of the intervention. Two-factor repeated measures ANOVA was used to compare the treatment differences between the two groups. Results: After 12 weeks of the intervention period, social health was significantly improved in the exercise group (P < 0.01), and there was a statistically significant difference in mental health scores between exercise group and control group, with a greater impact in exercise group.( Psychology: P < 0.01; SAS: P < 0.01; SDS: P < 0.01; PSQI: P < 0.01), physical health improved in the exercise group, physiology (P < 0.01), symptom (P < 0.01), heart rate (P < 0.01), systolic blood pressure (P < 0.01), systolic blood pressure (P < 0.01), vital capacity (P < 0.05), grip (P < 0.01), vertical jump (P < 0.001), sit and reach (P < 0.01), 50-meter run (P < 0.01), and reaction time (P < 0.01). Conclusions: Aerobic exercise intervention is an effective treatment for MA-dependent individuals, and the 12-week intervention improved the social, physical, and mental health of MA-dependent individuals. We recommend that future studies focus more on drug-dependent individuals' overall health status rather than just relapse. Clinical Trial Registration: ChiCTR2200055348. Registered on January 07, 2022. https://www.chictr.org.cn/hvshowproject.aspx?id=131048.